Factors Related to Teacher Resilience during COVID-19 - Marshall, David T.; Shannon, David M.; Neugebauer, Natalie M.; Love, Savanna M. (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2023)
Teaching during the 2020–2021 school year was fraught with challenges related to the COVID-19 pandemic. In the United States, teacher experiences varied greatly. Teacher attrition has been a concern for years, and contemporary media outlets reported that this was exacerbated by the pandemic. The authors surveyed teachers nationally between January and February 2021 (n = 334) to uncover what factors were related to teachers’ reported intention to remain in the classroom after the 2020– 2021 school year. Logistic regression findings indicate that teachers approaching retirement age and those teaching in private schools were significantly less likely to report an intention to remain at their school while elementary school teachers were more likely to stay. Conversely, we found that teacher autonomy, job satisfaction, and student access to resources outside of school were all positively associated with an intention to remain in their current position.